Strategy for Priority Setting, Monitoring and Evaluation - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
This document shows how CCAFS is dealing with monitoring and evaluation (M&E), and to demonstrate the cascade from the overarching logframe down to project activities in specific sites.